Mindfulness meditation as a tool for enhancing recovery and reducing burnout in elite tennis players - Liao, Min (Frontiers in Psychology, 2025)
IntroductionThis research determines mindfulness meditation promotes psychological recovery and lessen burnout amongst top-level tennis athletes. It also examines the modifying effect of psychological resilience on this association.MethodsThe use of a quantitative cross- sectional design was used where 120 of the top and famous tennis players participated (mean age = 24.8 years). They were asked to fill in validated surveys that assessed mindfulness meditation, recovery, burnout, and psychological resilience. The analysis of data was carried out through structural equation modeling with SmartPLS 4 that was used in order to test direct, indirect, and interaction effects.ResultsStructural equation modeling identified the relationship to be significant among the variables. The Mindfulness meditation has had a positive connection with recovery (β = 0.42, p < 0.001) and a negative relationship of burnout (β = –0.30, p < 0.001). The relationship between mindfulness meditation and the burnout was mediated by (partially) recovery (β = –0.19, p < 0.001). Mindfulness meditation had a significant effect on recovery (β = 0.42, p < 0.001) and psychological resilience moderated its effects (β = 0.22, p < 0.01), whereby more resilient athletes enjoyed more effects of mindfulness meditation. The model accounted to 41 percent variance in recovery and 53 percent in burnout.DiscussionThe value of mindfulness to the recovery process is complemented by the element of psychological resilience, and this aspect should not be underestimated in terms of its significance in competitive sports settings.